2013
DOI: 10.3325/cmj.2013.54.192
|View full text |Cite
|
Sign up to set email alerts
|

Impact of extended course duration and stricter study organization on attrition and academic performance of medical students

Abstract: AimTo assess whether extended medical school duration, block/modular structure of subjects, not allowing students to transfer exams into the higher course year, and curriculum implementation in line with the Bologna Accord are associated with lower attrition and better academic outcomes of medical students.MethodsWe retrospectively investigated curricula at the University of Split School of Medicine and academic outcomes of 2301 medical students during a 33-year period (1979-2011). The following data were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…One limitation of our study is that we do not know which of the six interventions contributed most to the observed results. Based on a previously published study in which we showed that stricter regulations were associated with better academic outcomes for medical students, [ 17 ] we assume that the most important interventions were related to more stringent study regulations in the form of mandatory progress reports, obligatory completion of a detailed research plan by the end of the first study year, higher year enrollment regulations and the possibility of being expelled if exams were not passed within two years.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of our study is that we do not know which of the six interventions contributed most to the observed results. Based on a previously published study in which we showed that stricter regulations were associated with better academic outcomes for medical students, [ 17 ] we assume that the most important interventions were related to more stringent study regulations in the form of mandatory progress reports, obligatory completion of a detailed research plan by the end of the first study year, higher year enrollment regulations and the possibility of being expelled if exams were not passed within two years.…”
Section: Discussionmentioning
confidence: 99%
“…These reasons are perhaps the reflection of the prominent resignation among students, but also in society as a whole. Moreover, medical professionals, after long and demanding studies ( 21 ), are often faced with low salaries, heavy workloads, remuneration not related to performance, and poor career prospects ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…An issue which is up to now less investigated is the influence of the study duration on the academic performance. In this field, a Croatian group reported on the positive influence of an extended study duration from five years to six years [9]. However, this Croatian study is related to the regular study duration and not on the individual study duration, which can be longer.…”
Section: Introductionmentioning
confidence: 99%